Religious Diversity and Blasphemy Law: Understanding Growing Religious Conflict and Intolerance in Post-Suharto Indonesia - Noorhaidi Hasan (Al-Jami'ah Research Centre, 2017)
This paper will look at how the explosion of militant religious activism and violence against minorities in post-Suharto Indonesia is embedded in the state’s failure to apply a proper management of religious diversity and civic pluralism. In the bottom of this issue lies controvertial Law No. 1 of 1965 on the prevention of the abuse or insulting of a religion, known as the Blasphemy Law. Debates have abounded on the extent to which the Law has transgressed the principles of religious freedom guaranteed by the Indonesian Constitution. This paper will thus also examine petitions filed by human rights activists and civil society organizations to demand judicial reviews of the Law before the Constitutional Court[Artikel ini akan menjelaskan bagaimana militansi aktifis agama dan kekerasan terhadap minoritas pasca Soeharto yang muncul akibat kegagalan Negara dalam mengelola keragaman agama dan pluralitas masyarakat. Dasar dari persoalan ini berpangkal pada kontroversi UU No. 1 Tahun 1965 tentang Pencegahan Penyalahgunaan dan/atau Penodaan Agama atau yang dikenal dengan UU Pencemaran Agama. Perdebatan yang panjang telah mengarah pada pelanggaran prinsip hukum mengenai jaminan kebebasan agama oleh konstitusi. Artikel ini juga akan membahas petisi yang diajukan oleh aktifis HAM dan ornop untuk mengajukan judicial reviews ke Mahkamah Konstitusi.]